Management of a Giant Thyroid Goiter in Limited Resources Hospital: A Case Report - Muhammad David Perdana Putra; Rakhman Wahyudi Mulyo; Ibnu Kharisman; Agus Murdianto; Sri Wiwoho Mudjanarko (Devotion : Journal of Research and Community Service, 2026)
Giant thyroid goiters remain a health problem in areas with limited access to primary health care. Delays in diagnosis and treatment can lead to progressive enlargement, compressive symptoms, and greater surgical challenges. This case report aimed to describe the management of a giant thyroid goiter in a hospital with limited resources. A 61-year-old man presented to the surgical outpatient clinic at Dr. Darsono Pacitan Regional General Hospital with a large mass on the right anterior side of the neck that had been present for 20 years. Initially, the mass was approximately the size of a thumb, but it gradually enlarged to approximately 10 × 10 × 8 cm. Physical examination revealed a firm, lobulated mass that moved with swallowing, extending from below the chin to the suprasternal notch, accompanied by dilated superficial blood vessels. The patient also reported dysphagia, shortness of breath that had begun five days before the examination, and hoarseness that had persisted for five years. No cervical lymphadenopathy, history of radiation exposure, chronic disease, previous surgery, or family history of similar disease was found. Based on the compressive symptoms and the very large size of the mass, unilateral thyroidectomy was performed with good outcomes. This case demonstrates that a giant multinodular goiter can cause compressive symptoms and present surgical challenges; however, it can still be safely managed through a well-planned unilateral thyroidectomy.